Analysis of campus building energy optimization based on energy plus software simulation / Chi Yi Ming - Chin, Yi Ming (2018)
This research project presents the idea of campus building energy optimization strategies according to the nature of building and occupants’ activities. World have been experiencing rapid growth for last few decades and thus cause the energy consumption rise drastically. Therefore, the objectives of this research are to propose the energy optimization approaches: set-point temperature and tinted window for campus building. The approaches were built according to the target building characteristic and focus and thermal consumption only. Energy consumption of the target building was simulated using energy simulation software (EnergyPlus) and the result was compared. The approaches proposed were verified using the software respectively. Simulation result shows that both approaches had successfully reduced the total building energy consumption by reducing HVAC system energy consumption. Set-point temperature reduced the annual energy consumption by 10.05% whereas tinted window would reduce the annual energy consumption by 3.25%. The results proved that the two optimization strategies could effectively reduce the cooling load and total energy consumption of the campus building.